2022
DOI: 10.3389/fsufs.2022.940900
|View full text |Cite
|
Sign up to set email alerts
|

Pyracantha fortuneana (Maxim.) Li: A comprehensive review of its phytochemistry, pharmacological properties, and product development

Abstract: Pyracantha fortuneana (Maxim.) Li has been used as a herbal medicine in China in its long history. Since ancient times, the fruits of P. fortuneana has been considered a functional food to improve various diseases. Many bioactive substances, including proanthocyanidins, phenols, polysaccharides, and dietary fibers, have been isolated and identified from the P. fortuneana, which possess diverse biological properties both in vitro and in vivo. Although the researches on the P. fortuneana have achieved extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 163 publications
1
4
0
Order By: Relevance
“…As the fruits mature, the TPC gradually decreases, suggesting oxidation of phenolic compounds. This is consistent with previous reports that found higher polyphenolic content in immature fruits (Wang et al, 2022;Wei et al, 2017). Other studies have reported a wide range of TPC in mature wild P. fortuneana fruits, ranging from 42.03 mg to 74.42 mg GAE/g (various drying methods), 9.67 ± 0.32 mg GAE/g (90% methanol extraction), 9.67 ± 0.32 mg GAE/g (70% methanol extraction), and 17.33 ± 0.35 mg GAE/g (50% acetone extraction) (Lawag et al, 2023;Wang et al, 2019), indicating variations in phenolic composition even within the same P. fortuneana species, possibly due to different extraction methods, drying methods, or climate conditions.…”
Section: Tpc Tfc Tac Antioxidant Activity and Tyr Inhibitory Activity...supporting
confidence: 94%
See 2 more Smart Citations
“…As the fruits mature, the TPC gradually decreases, suggesting oxidation of phenolic compounds. This is consistent with previous reports that found higher polyphenolic content in immature fruits (Wang et al, 2022;Wei et al, 2017). Other studies have reported a wide range of TPC in mature wild P. fortuneana fruits, ranging from 42.03 mg to 74.42 mg GAE/g (various drying methods), 9.67 ± 0.32 mg GAE/g (90% methanol extraction), 9.67 ± 0.32 mg GAE/g (70% methanol extraction), and 17.33 ± 0.35 mg GAE/g (50% acetone extraction) (Lawag et al, 2023;Wang et al, 2019), indicating variations in phenolic composition even within the same P. fortuneana species, possibly due to different extraction methods, drying methods, or climate conditions.…”
Section: Tpc Tfc Tac Antioxidant Activity and Tyr Inhibitory Activity...supporting
confidence: 94%
“…Therefore, the red fruits of P. fortuneana can be used to extract anthocyanins, and they can be a viable source of natural nutrients and anti‐visual fatigue food additives. In addition, the ripe fruits of P. fortuneana have abundant amino acid and polysaccharide components, which can be used as original materials or nutritional enhancers and processed into food products such as juice, jellies, beers, and chewable tablets (Li et al., 2022; Wang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both substances contain anti‐inflammatory activity. Second, arbutin, as an important active substance in Pyracantha japonicus, can relieve symptoms of urinary tract infections and reduce the need for antibiotics for the treatment of urinary tract infections (Wang et al., 2022). Pyracantha oil can significantly inhibit capillary permeability, inhibit exudation, reduce swelling, and increase phagocytosis.…”
Section: Biological and Medicinal Propertiesmentioning
confidence: 99%
“…This plant has also been processed as common products such as jelly, sauce, base wine, and jam (Chari et al., 2020). Pyracantha is used in folk medicines to treat symptoms such as accumulated food and diarrhea (Wang et al., 2022). To treat bodily pain, Pyracantha roots are boiled and harvested in the Limpopo Province of South Africa (Semenya et al., 2012).…”
Section: Application and Patents Of Pyracanthamentioning
confidence: 99%